The role of the pediatrician in youth violence prevention - Soon Ki Kim; Nam Su Kim (Korean Pediatric Society, 2013)
School bullying has become a major social problem in Korea after the emergence of media reports on children who committed suicide after being victimized by bullies. In this article, we review the characteristics of bullying, and investigate the role of the pediatrician in the prevention of and intervention against bullying and school violence. Bullying can take on many forms such as physical threat, verbal humiliation, malicious rumors, and social ostracism. The prevalence of bullying in various countries is approximately 10% to 20%. In Korea, the prevalence of school violence is similar but seems to be more intense because of the highly competitive environment. From our review of literature, we found that children who were bullied had a significantly higher risk of developing psychosomatic and psychosocial problems such as headache, abdominal pain, anxiety, and depression than those who were not bullied. Hence, it is important for health practitioners to detect these signs in a child who was bullied by questioning and examining the child, and to determine whether bullying plays a contributing role when a child exhibits such signs. Pediatricians can play an important role in the prevention of or intervention against school violence along with school authorities, parents, and community leaders. Moreover, guidelines to prevent school violence, such as the Olweus Bullying Prevention Program, KiVa of the Finish Ministry of Education, and Connected Kids: Safe, Strong, Secure of the American Academy Pediatrics, should be implemented.